2011
DOI: 10.2147/ijwh.s24424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori infection on pregnancy rates and early pregnancy loss after intracytoplasmic sperm injection

Abstract: Background:There is a need to elucidate what affects the implantation and early pregnancy course in pregnancies conceived with assisted reproductive technology (ART) so that pregnancy rates and outcomes can be improved. Our aim was to determine the role of maternal Helicobacter pylori infection.Material and methods:We did a prospective study of 187 infertile couples undergoing intracytoplasmic sperm injection (ICSI) and segregated those according to underlying infertility etiology. We assessed the status of H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(36 reference statements)
0
6
1
Order By: Relevance
“…Bahceci & Ulug (2004) found no significant association between cause of infertility and rate of early miscarriage. This is not consistent with the results described by Hajishafiha et al . (2011), in a study that found a significant relationship between the causes of infertility and the rate of miscarriage.…”
Section: Discussioncontrasting
confidence: 99%
“…Bahceci & Ulug (2004) found no significant association between cause of infertility and rate of early miscarriage. This is not consistent with the results described by Hajishafiha et al . (2011), in a study that found a significant relationship between the causes of infertility and the rate of miscarriage.…”
Section: Discussioncontrasting
confidence: 99%
“…However, endogenous uterine AP may not be sufficient during chronic or an inordinate levels of LPS. Intrauterine and systemic infections have been linked to the incident of early pregnancy losses (EPLs) and preterm births (PTBs) from pregnancies achieved naturally or by assisted reproductive technologies [ 1 , 68 , 69 ]. Results from clinical studies using antibiotics to reduce the rate of EPL and PTB by killing bacteria were mixed and disappointing [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association between H. pylori and LBW has been suggested [ 13 , 14 ]. However, there is limited data on association between H. pylori and birth weight especially in developing countries.…”
Section: Introductionmentioning
confidence: 99%